(untitled) (Global Journal of Human-Social Science, 2021)
Epics Argonautica and Medea were written in the Greek language a nd the epic Silappathikaram was written in the Tamil language Even though these epics were written in two different languages both mention the Kingdom of Pandion More than that the epics in both these languages exhibit heroism one in a pair proficiency of music extreme affection for husband and the theory of fate and chastity Above all they also mention about their foreign trade contacts The Greek myth mentioned about the lack of clarity in the sorrow happenings and it authorised the house of the God which is not understandable The Tamil philosophy mentions that according to the action of the individual he or she gets happiness or sorrow So the reason for the sorrow is not in the hands of the God as in Greek but with the human being oneself